PENGARUH PELAKSAAN PROGRAM KESEJAHTERAAN TERHADAP DISIPLIN KERJA KARYAWAN ASKES - Jasman Saripuddin S.E., M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study aims to determine whether the implementation of welfare programs capable of creating an effective employee discipline and know how to influence the implementation of wellness programs to employees of companies in improving employee discipline.